Pengaruh Kompres Kubis Terhadap Breast Engorgement Ibu Postpartum Sectio Caesarea - Yuni Astuti; Tuti Anggarawati (Universitas Ngudi Waluyo, 2019)
Sectio caesarea is a delivery by making an incision in uterus through the frontwall of the abdomen. Sectio caesarea actions cause pain due to surgery. She also had pain, fatigue and prolonged labor process can cause breast engorgement. Engorgement is a condition where the breasts become full due to static ASI lymphatic flow, increased congestion and vascularity, and can lead toaccumulation of intra-caudal pressure that will affect the segment of the breast so that the whole pressure increased breast. Non-pharmacological management used to overcome this problem is to use cabbage compresses. Cabbage leaves contain an amino acid that is believed to reduce the breast engorgement. This study aims to determine the effect of cabbage compress to decrease breast engorgement scale of post partum section caesarea. This study used a quasi-experimental research design with a one group pre-post test design. Sampling technique with consecutive sampling. Population in this study were post partum section caesarea with breast engorgement in Rumkit Bhakti Wira Tamtama from June to August 2017. The analysis using the Wilcoxon test. Results has difference in scale breast engorgement before and after cabbage compress on postpartum maternal section caesarea with p value 0,001 (<0,05). Conclusion there are significant cabbage compress to decrease postpartum sectio caesarea with breast engorgement after compresses cabbage. This intervention is recommended to increase the comfort of post partum sectio caesarea with breast engorgement.